(3QSGdI aj JMbjb eQGO GdbGFdjf HCf Gddg JYGdi ehLH HGdPGJs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ChLO GdYGde HGdbOQI hGdENJjGQ hHYO agPg QSGdI ai JMbjb eQGO GdbGFdjf HCf GdhGLH JYGdi ehLH HGdPGJ hGYde Cf gPg GdeSCdI ef CegGJ eWGdH GdMceI s
(3BNQgG (B:s
(3Ke bGd aGUdM aGONd GdLfI dGf HfGg Ydi Gf dGjLNd GdLfI ef dGKhGH dg hdG UMI dg YfOge JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJhMjO hGdedd hGdfMds